An Exploration of the Differential Effects of Parents' Authoritarianism Dimensions on Pre-school Children's Epistemic, Existential, and Relational Needs - Guidetti, Margherita; Carraro, Luciana; Castelli, Luigi (Frontiers in Psychology, 2017)
Research on adult populations has widely investigated the deep differences that characterize individuals who embrace either conservative or liberal views of the world. More recently, research has started to investigate these differences at very early stages of life. One major goal is to explore how parental political ideology may influence children’s characteristics that are known to be associated to different ideological positions. In the present work, we further investigate the relations between parents’ ideology and children cognitive processing strategies within the framework of political ideology as motivated social cognition (Jost et al., 2003) and the dual process model of political ideology (Duckitt et al., 2002). Specifically, epistemic (implicit attitudes toward order vs. chaos), existential (negativity and threat bias), and relational needs (conformity measure) were assessed in pre-school children (N = 106; 4-6 years). For each child at least one parent completed both the Social Dominance Orientation (SDO) and the Right Wing Authoritarianism (RWA) measures. Interestingly, results indicated that mothers’ and fathers’ responses had unique associations with children’s socio-cognitive motivations, and different findings emerged in relation to the two facets of parental authoritarianism, namely dominance (i.e., SDO) and submission (i.e., RWA). More specifically, children’s existential needs appeared to be more related to mothers’ RWA scores, whereas children’s epistemic needs appeared to be more related to fathers’ SDO. Finally, parents’ RWA and SDO scores appeared to have opposite effects on children’s relational needs: children’s conformity increased at increasing levels of mothers’ RWA and decreased at increasing levels of fathers’ SDO. Overall, however, results were relatively weak and several links between the responses of parents and their children were not significant, suggesting caution in drawing strong conclusions about the impact of parents’ ideology. Limitations and future developments will be discussed.